Housing policies for Asia: A theoretical analysis by use of a demand and supply model - Naoyuki Yoshino; Matthias Helble; Toshiaki Aizawa (Asian Development Bank Institute (ADBI), 2015)
The main objective of this paper is to give an overview of the most commonly used housing policies and to illustrate their economic impact. To facilitate the analysis, we first introduce a simple two-period housing demand model for owner-occupied houses and rental houses. We then add a standard stock-flow housing supply model. Using this modelling framework, we explain the qualitative effects of various housing policies on supply and demand. In the last section of the paper, we provide a quantitative estimation of the impact of each policy and assess its effectiveness using a simple analysis of cost effectiveness. We hope that the model's versatility makes it a simple tool for policymakers to better understand the economic consequences of various housing policies.
Keywords: R21; R28; R31; R38; 330